Analysis of the marketing mix in the red brick business, Karanglegi Village, Trangkil District, Pati Regency - Rifa'atul Fauziah (Indonesia Accounting Research Journal, 2021)
This research is a qualitative  research with the type of field research (field research) and using two types of data sources, namely primary data and secondary data. The data was obtained using interviews, observation and documentation. After the data is collected, the next step is to analyze the data using a qualitative descriptive method. The results of this study state that the product mix in the red brick business includes product quality (sturdy, not easily broken, large size). Quality products are obtained from the selection of raw materials, manual printing processes, burning completely until cooked evenly. The price mix implements a price rebate strategy by providing discounts when buying on a large scale. In setting the price, the red brick craftsmen do not carelessly, but calculate the materials and market demand. They are members of the red brick craftsmen's association so that the prices of the craftsmen are the same (agreed). The distribution mix (place) includes the distribution channel for brick craftsmen in Karanglegi Village, which is carried out directly to consumers and also through intermediary agents, wholesalers and small traders. Promotion mix (promotion) carried out by red brick craftsmen through direct selling, advertising (radio, social media). Competition among craftsmen is done fairly. The marketing area that is reached by the Karanglegi brick craftsmen is the Pati Regency area, outside Pati Regency. The market segment for bricks in Karanglegi Village is the lower middle class, the upper middle class.